Hierarchical Concept to Build Value Co-Creation Gibson Guitar Community in Indonesia - Mario Saskara Pasamalangi; Mas Wahyu Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research connects the Consumer Culture Theory (CCT) perspective with the Service-Dominant Logic (S-D Logic) theory to show how to deeply understand brands through the eyes of consumers and the co-creation of brand culture to create value. The research method used is qualitative with ethnographic research design and in-depth interviews with key informants and the data analysis process using NVIVO 12 Plus to get comprehensive results. The final result of this study found the right model concept in implementing value co-creation hierarchically to support the sustainable growth of the Gibson Guitar brand.